Penentuan Pola Tanam Tanaman Pangan Berdasarkan Neraca Keseimbangan Air di Kecamatan Umbu Ratu Nggay Barat, Kabupaten Sumba Tengah, Provinsi Nusa Tenggara Timur - Nganji, Marten Umbu; Simanjuntak, Bistok Hasiholan (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2020)
Cropping pattern is an agricultural business activity to obtain maximum results taking into account climatic and soil conditions . Setting the cropping patterns is part of planning agricultural activities to reduce the risk of crop failure. Planning and suitability of cropping pattern depends on the size of rainfall in certain areas. This study is aimed to determine the food cropping patterns of food crops based on the balance of water balance in west Umbu Ratu Nggay District, Central Sumba Region. This research was conducted in West Umbu Ratu Nggay District with method of primary and secondary data, and continued laboratory analysis . The data used are soil texture, soil temperature, air temperature, soil binding capacity and monthly rainfall data for the last ten years. The balance of water conditions culculated by using jNSM (Java Newhall Simulation Model), followed by geographic information system software (GIS) to map the area experiencing surplus period of groundwater deficit areas to be able to determine alternative cropping pattern. Based on the calculation of the water balance, an alternative cropping pattern is obtained for Umbu Ratu Nggay Barat sub-district with an average of sufficient water supply (surplus) in a different region from the choice of plants, namely the first area with the choice of sweet potato-bero; rice-bero and/or corn-bero with an area of 588.83 ha (2.09%). The second area with alternative plant choices is sweet potato-bero; rice-green beans-bero; corn-green beans-bero with an area of 7,856.96 ha (27.95%). The third area with alternative plant choices is sweet potato-bero; rice-rice-bero; rice-corn-bero; rice-green beans-bero; corn-corn-bero; corn-green beans-bero with an area of 19,662.96 ha (69.96%).